Implementation of the Utilization of the Identifikasi, Refleksi, and Benahi (IRB) Approach to Education Report Cards in an Effort to Improve Literacy - Fidya Junisya; Tri Widayatsih; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to describe the application of the Identifikasi, Refleksi, and Benahi (IRB) approach, utilizing Education Report data, to enhance literacy at SDN 223 Palembang. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation, focusing on four aspects: planning, implementation, supervision, and improvement strategies. The results demonstrate that data-driven, collaborative planning and participatory program implementation including daily reading sessions and literacy-integrated learning significantly strengthened students' literacy skills and the school's reading culture. The novelty of this research lies in its detailed case study of the IRB framework as an adaptive, cyclical model for data-based educational management in a primary school setting. A key practical implication is the provision of a replicable blueprint for other schools to systematically transform assessment data into targeted literacy interventions. The study contributes a validated, holistic strategy to the field of school improvement, emphasizing that sustained literacy gains are achievable through structured collaboration, continuous reflective supervision, and capacity-building across the entire school community.